MALDIG: MULTIMEDIA LOKAL DIGITAL UNTUK MENINGKATKAN MATERI KONSEP GEOGRAFI PADA IPAS-SD (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop digital-based science learning media through the 4D procedure involving three elementary schools in Malang. The research subjects consisted of 45 fifth-grade students, teachers, and experts. The define stage showed variations in student characteristics, with SDN A having 60% weak categories, 20% standard, and 20% understanding; SDN B having 53.33% weak categories, 20% standard, and 26.67% understanding; SDN C having 40% weak categories, 20% standard, and 40% understanding. The design stage resulted in different media preferences, namely color videos, animated games, and digital-based materials. Media design was carried out using Canva, Adobe Premiere, and stop motion techniques to improve the appearance, audio, and interactivity. The develop stage showed that the media created was interesting, creative, easy to understand, and increased learning motivation. Integrated materials, games, and competency test sheets facilitate student access. Expert validation yielded scores of 91% from media experts, 93% from language experts, and 90% from material experts, declaring the media highly valid and suitable for use. The dissemination phase was conducted through fifth-grade teachers at the three schools, and introduced through YouTube and the Temuguru forum. The experts recommended further development to turn the media into an app for offline access.